Evaluating Ocean Literacy of Elementary School Students: Preliminary Results of a Cross-Cultural Study in the Mediterranean Region - Mogias, Athanasios; Boubonari, Theodora; Realdon, Giulia; Previati, Monica; Mokos, Melita; Koulouri, Panayota; Cheimonopoulou, Maria Th. (Frontiers in Marine Science, 2019)
A good understanding of the role and function of the ocean seems to be of paramount importance in recent years, constituting the basic tool for the promotion of healthy and sustainable marine environment, and a target area of the 2030 Agenda for Sustainable Development. In this study, the content knowledge of elementary school students (grades 3-6) in regards to ocean sciences issues was examined. A structured questionnaire was administered to 1004 students participating in a cross-cultural study from three Mediterranean countries (Italy, Croatia, and Greece). The results of the study indicated a rather moderate level of knowledge in the total sample, while slight differences were recorded among the three countries revealing common knowledge gains and misconceptions. Rasch analysis was applied to further evaluate the validity of the results, while the influence of certain demographics on students’ knowledge level was also investigated. This study concludes with a discussion of the implications on national curriculum development in elementary education level, in order to promote ocean literacy and to ensure protection and conservation of the Mediterranean Sea.